A note on how and why ‘state + aorist = achievement’ - Fábregas, Antonio (Onomázein, 2016)
In syntactic and semantic studies, there is a debate about the proper definition of ‘achievement’. While some authors consider them pure punctual boundaries without any extension, others treat them as short accomplishments, and propose that they have a process component that happens to be instantaneous. The goal of this article is to discuss an empirical pattern whereby some stative verbs become achievements in the aorist; it is argued that this pattern of data supports the view of achievements as pure boundaries.